Exotic Toys, Musical Centralities and Power Reversals: The Early Reception of European Keyboard Music and Instruments in East Asia 20 - Chen, Jen-yen (Chopin Review, 2023)
Western music first achieved a sustained presence in East Asia during the sixteenth century, brought to this ‘distant’ region by European traders and missionaries. However, its dissemination remained limited for some three centuries to specific locales such as the area of southern Japan around Nagasaki and the Chinese imperial court in Beijing. Even so, investigation of the early phases of this cross [1]cultural encounter helps to illuminate the process by which Asian listeners gradually assimilated the alien quality of Europe’s musical sounds as transmitted especially by its keyboard instruments, to such a degree that these came to function as a native language of sorts. The present article will discuss the following aspects: the exotic fascination with the technological complexity of the foreigners’ musical devices, taking precedence over any aesthetic engagement with the music; the initial clash and then shift in musical centralities in the sense formulated by Bruno Nettl, that is, the selective emphasis of parameters (e.g. polyphony, timbre) that define musical creation, listening and thought; the applicability to the history of Sino-Western exchange of Emily Dolan’s notion of ‘keyboardisation’, an idiosyncratic reconceptualisation of musical content that would eventually acquire normative force; questions of colonisation and reverse colonisation in understanding the complex power dynamics that shaped this global musical encounter.